The Role of Endoplasmic Reticulum Stress in Gastroesophageal Reflux Disease Symptoms and Treatment - Kasap, Elmas; Buran, Tahir; Toraman Avcu, Aysun; Solmaz Hasdemir, Pınar; Balcan, Erdal; Aktan, Çağdaş; Korkmaz, Mehmet (Turkish Journal of Gastroenterology, 2023)
Background: Gastroesophageal reflux disease is a common condition worldwide. There is no curative treatment for gastroesophageal reflux disease. Endoplasmic reticulum stress leads to the activation of the unfolded protein response and has an important role in inflammation. The aim is to determine the role of endoplasmic reticulum stress in the follow-up of individuals with gastroesophageal reflux disease and the temporal changes of endoplasmic reticulum stress markers with treatment. Methods: Twenty-four subjects in total were recruited prospectively, of whom 15 had nonerosive reflux disease. Two biopsies from 2 cm above the esophagogastric junction, 2 biopsies from gastric antrum mucosa, and 2 biopsies from gastric corpus mucosa were taken. Simultaneously, 2 tubes of venous blood samples were drawn from each individual (1 tube for studying the genetic markers and 1 tube for analyzing the CYP2C19 polymorphism). Results: The mean age was 42.3 ± 17.6 for women and 34.66 ± 11.2 for men. Pantoprazole, esomeprazole, rabeprazole, and lansoprazole preparations were used for treatment. There was no significant difference between tissue and blood samples for panel genes ATF-6, XBP-1, DDIT-3, DNAJC-10, and EIF-2-AK before treatment. There was a significant decrease in the level of ATF-6, XBP-1, DNAJC-9, EIF2-AK, and NF-2L-2 genes in blood after treatment. In the comparison of proton pump inhibitors, significant decreases in the expression of the ATF-6, XBP-1, and DNAJC-9 mRNAs were detected in blood from individuals after treatment. Conclusion: Endoplasmic reticulum stress can be for evaluating the clinical improvement and the effectiveness of treatment in gastroesophageal reflux disease. Cite this article as: Kasap E, Buran T, Toraman Avcu A, et al. The role of endoplasmic reticulum stress in gastroesophageal reflux disease symptoms and treatment. Turk J Gastroenterol. 2023;34(5):533-541.